EU biofuel policies in practice: A carbon map for the Brazilian Cerrado - Mareike Söder (Kiel Institute for the World Economy (IfW), 2014)
It is still difficult for biofuel producers to prove the contribution of their biofuels to reducing carbon emissions because the production of biofuel feedstocks can cause land use change (LUC), which in turn causes carbon emissions. A carbon map can serve as a basis to prove such contribution. I show how to calculate a carbon map according to the sustainability requirements for biofuel production adopted by the European Commission (EU-RED) for the Brazilian Cerrado. Based on the carbon map and the carbon balance of the production process I derive maps showing the possible emission savings that would be generated by biofuels based on soy and sugarcane if an area were to be converted to produce feedstock for this biofuel options. I evaluate these maps according to the criterion contained in the EU-RED of 35% minimum emission savings for each biofuel option compared to its fossil alternative. In addition, to avoid indirect LUC effects of the EU-RED that might offset any contribution of biofuels to reducing carbon emissions. I argue that all agricultural production should be subject to a carbon assessment. In this effort, the calculated carbon maps can be the basis for a climate friendly land use planning that is binding for all agricultural production in the Cerrado.
Keywords: Q42; Q58; Q56; Q16; 330; biofuels; carbon emissions; Renewable Energy directive; carbon map; land use change; Brazil